Impact of internal corporate governance mechanisms on Enterprise value: evidence from listed companies in Sri Lanka - Balagobei, S.; Velnampy, T. (Eastern University, Sri Lanka, 2023)
Corporate governance is crucial for gaining investor confidence and unlocking shareholder value. The aim of the study is to examine the influence of internal corporate governance mechanisms on enterprise value of listed companies in Sri Lanka. This study is confined to listed companies using a sample of 104 companies in Sri Lanka with 728 firm-year observations during the period of 7 years from 2015 to 2021. The statistical techniques of Pearson’s correlation and Generalized Methods of Moments (GMM) were used to analyze the association between internal corporate governance mechanisms and enterprise value. The findings of this study revealed that board size positively influences the enterprise value of listed companies in Sri Lanka whereas Chief Executive Officer Duality (CEOD) and managerial ownership have a negative influence on enterprise value. Board independence, board diversity, board activity and audit committee size have not shown any significant influence on enterprise value. Moreover, control variables, firm size, firm age and leverage have positive effects on enterprise value. These findings have implications for managers, policymakers, researchers and investors in general and those in developing countries in particular. This paper offers contributions to both literature and practice on what internal corporate governance dimensions are important to enhance the enterprise value of listed companies.
Keywords: Corporate governance; Board size; Enterprise value; Managerial ownership JEL classification: G32